Preliminary perceived intervention changes and engagement in an evidence-based program targeted at behavioral inhibition during early childhood, delivered in-person and online - Guedes, Maryse; Maia, Rita; Matos, Inês; Antunes, Marta; Rolão, Teresa; Chronis-Tuscano, Andrea; Rubin, Kenneth H.; Veríssimo, Manuela; Santos, António J. (Frontiers in Psychology, 2023)
Behavioral inhibition during early childhood is one of the strongest risk factors for the development of later anxiety disorders. Recently developed in-person interventions that target both young children who are highly inhibited and their parents (e.g., the Turtle Program), have decreased children’s anxiety and have increased social participation in the peer group. However, researchers have yet to examine the effects of intervention mode of delivery. In the present study, we: compared the pre-to post-intervention changes in child and parenting functioning of families participating in the Turtle Program, delivered in-person and online with those changes made in families allocated to a waiting-list condition; compared session attendance, homework completion and satisfaction with the intervention outcomes of families involved in the Turtle Program, delivered in-person and online; and explored the predictive role of parenting and child factors in session attendance, homework completion and satisfaction with the outcomes of families involved in the Turtle Program, depending on the mode of delivery (in-person vs. online). Fifty-seven parents of highly inhibited preschoolers (3-5 years), with no diagnosis of selective mutism or developmental disorders, who were randomly allocated to waiting-list (n = 20), Turtle Program delivered in-person (n = 17) and online (n = 20) conditions completed the Portuguese versions of the Behavioral Inhibition Questionnaire, the Preschool Anxiety Scale, the Social Behavior and Competence Scale, the Modified Child-Rearing Practices Questionnaire at pre- and post-intervention assessment. Parents also completed the Preschool Shyness Study Satisfaction Survey at post-intervention assessment. Independent of intervention mode of delivery, generalized equation estimates revealed a reduction in children’s total anxiety symptoms and an improvement in parental nurturing behaviors. Child anxiety and social competence at pre-assessment were the most prominent predictors of session attendance and satisfaction with post-intervention child and parenting outcomes. Overall, this study showed that parents in both intervention conditions perceived comparable positive changes in child functioning from pre- to post-intervention assessment and similar levels of session attendance, homework completion, and satisfaction. Significantly, however, perceived satisfaction with post-intervention child and parenting outcomes was higher, when children were reported to display higher SEL skills at baseline, independent of the intervention mode of delivery